Tissue-Specific Antioxidant Activities of Germinated Seeds in Lentil Cultivars during Thermal Processing - Ji Hye Kim; Shucheng Duan; You Rang Park; Seok Hyun Eom (MDPI AG, 2023)
Nongerminated seeds (NGS) and germinated seeds (GS) of lentils are regularly eaten after thermal processing. However, the effect of these high temperatures on the beneficial antioxidants present in seeds is unknown. This study examined the effects of thermal processing on the color, polyphenol content, and antioxidant activity (AA) of the seeds of three different cultivars of lentils, including two with seed coats, French green (FG) and Lentil green (LG), and one without a seed coat, Lentil red (LR). Regardless of the cultivars and processing temperatures, the GS tended to be clearer and less yellow than the NGS. The GS of the FG and LG showed lower levels of total phenolic content, major flavonoid content (kaempferol, luteolin, and myricetin), and AA than the NGS. On the other hand, the LR displayed the opposite trend, with the above indicators being higher in the GS than in the NGS. As the values in the germinated endosperm tended to increase, it was concluded that the decrease in AA in the FG and LG was caused by the reduction in antioxidants in the seed coat. Although the temperature had nonsignificant effects on the majority of the antioxidants in the NGS and GS of different lentil cultivars, an 80 °C treatment yielded the highest value of AA in the GS of FG and LG. The results of a correlation coefficient analysis demonstrated the significance of the content of kaempferol, total flavonoids, and total phenolics examined for this experiment as contributors to AA in lentil tissues.